OPTIMASI MATERIAL REMOVAL RATE (MRR) BAJA ST 42 PADA PROSES CNC TURNING DENGAN MENGGUNAKAN METODE TAGUCHI - -, Arfendi; -, Napitupulu; Pranandita, Nanda (Jurnal Ilmiah Teknik Mesin, 2021)
Abstract High MRR is a goal to be achieved in the workpiece machining process using CNC turning. But the slow process will affect the processing time of the product, and will increase production costs. To overcome this, it is necessary to set appropriate process parameters to produce the most influential contribution to MRR and also to produce optimum parameter values. The purpose of this study was to determine the effect of parameters (cutting speed, spindle speed and depth of cut) on MRR and to determine the correct process parameter settings in order to produce optimal MRR on ST 42 steel. The study was conducted using ST 42 steel and using carbide chisels on CNC turning process. The process parameters that will be varied are spindle speed, feeding motion, and infeed depth. The experimental design used was orthogonal matrix L9(33). The repetition is done twice. Furthermore, the optimization of multi-response characteristics is carried out using the S / N Ratio method. From the research results, it was found that in order to reduce the variance of the response simultaneously, the infeed depth had the largest percentage contribution value, which was 46.642%, the spindle speed had a percentage contribution value of 14.362%, and then the feeding motion with a percentage contribution value of -7.548 And to obtain the optimal MRR of the workpiece, the spindle speed is set at 1500 rpm, the feeding motion is set at 0.5 mm / put, and the infeed depth is set at 1 mm. Keywords: Carbide, CNC Turning, Taguchi, S/N Ratio, MRR